2021
DOI: 10.1101/2021.09.14.460286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reward enhances memory via age-varying online and offline neural mechanisms across development

Abstract: Reward motivation enhances memory through interactions between mesolimbic, hippocampal, and cortical systems - both during and after encoding. Developmental changes in these distributed neural circuits may lead to age-related differences in reward-motivated memory and the underlying neural mechanisms. Converging evidence from cross-species studies suggests that subcortical dopamine signaling is increased during adolescence, which may lead to stronger memory representations of rewarding, relative to mundane, ev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…Overall, our results add to previous findings showing that individual differences in systems-level interactions differentially or selectively predict high-reward memory, in comparison to low-reward memory, where these effects were interpreted in light of a selective stabilisation of high-value memories (Cohen et al, 2021; Gruber et al, 2016; Murty et al, 2017). Other studies (Cohen et al, 2021; Gruber et al, 2016; Murty et al, 2017) investigating consolidation processes supporting memories for high-value information have manipulated value (i.e., incentives for intentional encoding or rewards in an unrelated task during incidental encoding) using within-subject manipulations. On the other hand, our study used a between-subject manipulation where half of the participants were informed that correct responses would be associated with additional monetary bonus payments.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Overall, our results add to previous findings showing that individual differences in systems-level interactions differentially or selectively predict high-reward memory, in comparison to low-reward memory, where these effects were interpreted in light of a selective stabilisation of high-value memories (Cohen et al, 2021; Gruber et al, 2016; Murty et al, 2017). Other studies (Cohen et al, 2021; Gruber et al, 2016; Murty et al, 2017) investigating consolidation processes supporting memories for high-value information have manipulated value (i.e., incentives for intentional encoding or rewards in an unrelated task during incidental encoding) using within-subject manipulations. On the other hand, our study used a between-subject manipulation where half of the participants were informed that correct responses would be associated with additional monetary bonus payments.…”
Section: Discussionsupporting
confidence: 82%
“…The authors showed that in the absence of an overall increase in RSFC between HPC and midbrain from pre- to post-learning rest, individual differences therein positively predicted the reward-driven associative memory effect. That interindividual differences in changes in RSFC between HPC and midbrain can predict later associative memory for information presented in high-reward contexts was recently replicated in an intentional encoding paradigm with a memory test after 24h (Cohen et al, 2021). In sum, the results provide evidence that monetary rewards influence neural post-encoding processes supporting the preferred consolidation of stimuli associated with rewards.…”
Section: Monetary Incentives and Memory Consolidationmentioning
confidence: 89%
See 2 more Smart Citations